разложите на множители выражение

(2x-5)вквадрате-xвквадрате=

(5x-2)вквадрате-(x-1)вквадрате=

(4x+3y)вквадрате-(3x-4y)вквадрате=

(2x-4y)вквадрате-(5x+y)вквадрате=

1

Ответы и объяснения

2013-01-20T19:09:44+04:00

(2x-5)^2-x^2=(2x-5-x)(2x-5+x)=(x-5)(3x-5)

(5x-2)^2-(x-1)^2=(5x-2+(x-1))(5x-2-(x-1))=(5x-2+x-1)(5x-2-x+1)=(6x-3)(4x-1)=3(2x-1)(4x-1)

(4x+3y)^2-(3x-4y)^2=(4x+3y+(3x-4y))(4x+3y-(3x-4y))=(4x+3y+3x-4y)(4x+3y-3x+4y)=(7x-y)(x+7y)

(2x-4y)^2-(5x+y)^2=(2x-4y+(5x+y))(2x-4y-(5x+y)) =(2x-4y+5x+y)(2x-4y-5x-y) =(7x-3y)(-3x-5y)= -(7x-3y)(3x+5y)